Development of Business Processes in the Energy Sector - Biolcheva, Petya; Ivanov, Sotir; Valchev, Evgeni (Research Papers, 2022)
The energy sector is among the key sectors of the economy. In order to meet market dynamics, to comply with regulatory requirements and in particular the Green Deal, the sector needs to invest in innovation. To achieve higher quality of the final product is essential to ensure the continuity and the optimality of the business processes taking place in the energy companies. This can be ensured through their complete transformation, introducing them to the “Age of Artificial Intelligence”. This paper tracks the development of business processes and outlines the trend in the following years. It reveals key business processes for energy companies and shows how they can be significantly improved through the capabilities of artificial intelligence. In order to achieve full synchronisation in their management, the way in which they can be integrated is also shown. This ensures the creation of a complete product with clear interconnections and full functionality.
Keywords: Business processes; Process integration; Artificial intelligence; Perspectives; Energy